2022
DOI: 10.1037/pspp0000386
|View full text |Cite
|
Sign up to set email alerts
|

A mega-analysis of personality prediction: Robustness and boundary conditions.

Abstract: Decades of studies identify personality traits as prospectively associated with life outcomes. However, previous investigations of personality characteristic-outcome associations have not taken a principled approach to covariate use or other sampling strategies to ensure the robustness of personality-outcome associations. The result is that it is unclear (a) whether personality characteristics are associated with important outcomes after accounting for a range of background variables, (b) for whom and when per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 100 publications
3
63
0
Order By: Relevance
“…If childhood and adult personality traits equivalently predict future life outcomes, this would suggest the mechanisms linking traits measured at distinct points of individuals’ lives operate similarly and, ultimately, yield equal predictions of future outcomes. In support of this perspective, both childhood and adulthood personality assessments predict similar outcomes 5 , 6 , 8 , 11 .…”
Section: Does It Matter When We Assess Personality?mentioning
confidence: 67%
See 1 more Smart Citation
“…If childhood and adult personality traits equivalently predict future life outcomes, this would suggest the mechanisms linking traits measured at distinct points of individuals’ lives operate similarly and, ultimately, yield equal predictions of future outcomes. In support of this perspective, both childhood and adulthood personality assessments predict similar outcomes 5 , 6 , 8 , 11 .…”
Section: Does It Matter When We Assess Personality?mentioning
confidence: 67%
“…Since this trait was in fact reported on by parents in our study, its prominence in predicting outcomes could reflect the parents’ concern with managing the child’s behavior and avoiding parent–child conflict, thus perhaps over-reporting on or emphasizing this quality in their child. Agreeableness as a personality trait is related to outcomes in various domains, including interpersonal, social, and health outcomes 11 , 38 40 so it is not entirely surprising this possible childhood precursor of agreeableness is related to a vast number of outcomes as well. Furthermore, one empirically derived personality taxonomy for children, the Hierarchical Personality Inventory for Children (HiPIC 41 ), found that compliance represented a blend of benevolence and, more interestingly, conscientiousness.…”
Section: Discussionmentioning
confidence: 99%
“…This is necessary because pre-existing differences between prospective grandparents and non-grandparents in variables related to the development of the Big Five or life satisfaction introduce confounding bias when estimating the effects of the transition to grandparenthood (VanderWeele et al, 2020). The impact of adjusting for pre-existing differences was recently emphasized in predicting life outcomes from personality (Beck & Jackson, 2022). Propensity score matching is one technique to account for confounding bias by equating groups in their estimated propensity to experience the event (Thoemmes & Kim, 2011).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Like life goals, personality traits are relatively stable constructs that influence how a person perceives and interacts with people and their environment (Bleidorn et al, 2022;. Moreover, personality traits are also robustly associated with many life outcomes (Beck & Jackson, 2022;Ozer & Benet-Martinez, 2006). Examining the mechanisms responsible for linking personality with life outcomes can yield insight into why life goals are associated with life outcomes.…”
Section: Possible Partner Effectsmentioning
confidence: 99%